Translation and validation of Marathi version of questionnaire for urinary incontinence diagnosis - Pawar, Anushree M.; Ganvir, Shyam D. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Urinary incontinence is a common health problem among women, which affects the quality of life. knowledge about the risk factors of urinary incontinence in this population will help us to take measures to reduce the burden of the condition. Questionnaire for urinary incontinence diagnosis (QUID) helps to distinguish type of incontinence. Methods: It was a community based cross-sectional study involving women living in the rural areas. A total of 25 women were taken for this study to find out reliability and validity of Marathi version of this questionnaire. Data was analysed with statistical package for the social sciences (SPSS) 20.0. Results: The internal consistency (homogeneity) was evaluated by Cronbach’s α coefficient, which was 0.795. validation was obtained from expert panel and the pilot testing showed that the questionnaire is acceptable. Conclusions: QUID Marathi version has been proven a reliable and valid tool for assessing urinary incontinence in women. It can be used as a quick screening tool for urinary incontinence in women of rural population.